Communities, abandonment and 'recognition': The case of post-state funding community bodies. (November 2016) - Fuller, Crispian
Abstract: Communities have increasingly been internalised as subjects with responsibilities in the delivery of urban policy and involvement in broader urban governance. A prominent example is the English New Deal for Communities (NDC) programme that ran between 2001 and 2012. Towards the end of government funding, NDCs were required to develop succession strategies that would leave a 'legacy' for their communities. This involved the development of social enterprise bodies that would continue to support community involvement and regeneration efforts through ownership of capital assets, acquisition of public service contracts, and partnership working with mainstream service providers. This paper examines the influence of communities on post-NDC bodies, and the relationship between these organisations and local government, which was a critical agent in the management of the previous NDC bodies. The 'recognition' perspective of Honneth (1995), which is concerned with the self-actualisation of actors through inter-subjective relations based on forms of recognition (e.g. respect), is deployed in the analysis of post-NDC bodies. The paper concludes that long term community representatives' have incorporated market values as a means in which to acquire 'respect' from social enterprise professionals, and that there is a lack of recognition by state agents of the role of post-NDC bodies in contemporary urban governance.